Expression of E-cadherin, N-cadherin, and Cytokeratin 18 and 19 in Placentas of Women with Severe Preeclampsia - Osman, Sahar E.; Salih, Magdi; Ahmed, Ehab M.; Mohammed, Ahmed A.; Adam, Ishag (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Although the exact mechanism leading to preeclampsia is not fully understood, abnormal trophoblast invasion contributes to its pathogenesis. Keratins and cadherin are known to play roles in the regulation of trophoblast proliferation. However, studies describing the association between keratins, cadherin, and preeclampsia are limited. AIM: The current study was conducted to investigate the association of these proteins with severe preeclampsia in Sudanese women. METHODS: A case–control study was conducted at Madani Maternity Hospital, Sudan. The cases included women with severe preeclampsia (n = 56) and healthy pregnant women as controls (n = 56). The assessment of keratin and cadherin was performed using immunohistochemical staining. RESULTS: There was no significant difference between the two groups in their mean age or parity. We found no significant differences in the expression of the markers E-cadherin, N-cadherin, or cytokeratin 18 and 19 in the placentas from individuals with preeclampsia versus controls. The number of placentas with severe preeclampsia versus controls expressing the E-cadherin, N-cadherin, cytokeratin 18, and cytokeratin 19 markers was 46 (82.1%) versus 46 (82.1%) (p = 0.988), 54 (96.4%) versus 48 (85.7%) (p = 0.121), 4 (7.1%) versus 0 (0%) (p = 0.126), and 11 (19.6%) versus 11 (19.6%) (p = 0.532), respectively. There was also no significant difference in the intensity of staining of these four markers (Ecadherin, N-cadherin, and cytokeratin 18 and 19) between severe preeclampsia and control placentas. CONCLUSION: Together, these results indicate that in this setting, the expression of E-cadherin, N-cadherin, CK18, and CK19 is not associated with severe preeclampsia.